The dynamics of macroeconomic indicators and stock market returns: An econometric perspective on advanced economies - Rudhani, Leonora Haliti; Hasanaj, Petrit; Rudhani, Taulant (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze and examine the short-term and long-term relationships between macroeconomic indicators and stock market returns in Switzerland, Sweden, and Denmark. The research is based on secondary data covering the period from 1927 to 2021. Using empirical analyses such as VAR, Granger causality, and VECM, the study confirms both short-term and long-term relationships between macroeconomic indicators and stock market returns. The results of the analyses indicate that economic growth has a significant positive relationship with stock market returns, while a long-term negative effect of this indicator was confirmed in Switzerland. The short-term interest rate had a negative relationship with stock market returns in the short term only in Denmark, but similar results were not confirmed for Sweden and Switzerland. Population growth showed a positive effect on stock market returns in Sweden and Denmark in the short term but not in Switzerland. Inflation was not found to be a significant indicator for stock market returns in any of the three countries.